Evidence from measuring community flood resilience in Asia - Laurien, Finn,Keating, Adriana (Asian Development Bank, 2019)
Disaster risk and subsequent loss and damage in Asia are increasing at an alarming rate, threatening socioeconomic gains. Arresting this rapid increase in exposure requires risk-informed development and urban planning - a challenging proposition complicated by multiple economic and political incentives. To reduce these risks, action at the national and regional levels must be complemented by action at the community level. Measuring community disaster resilience can help lead to novel and systemic investments that build community resilience. Our analysis of community flood resilience data finds deficiencies and potential for substantial improvements in community flood resilience investment across the region, with different recommendations for urban, peri-urban, and rural locations. Our evidence from case studies shows that interventions prioritized by the measurementinformed process are more likely to succeed and be sustainable and have cobenefits for community development.
10.22617/WPS190484-2
Keywords: Graue Literatur; assets and livelihoods; decision making; disaster; flood; measurement; resilience; wastemanagement